Synergistic effects in 3D honeycomb-like hematite nanoflakes/branched polypyrrole nanoleaves heterostructures as high-performance negative electrodes for asymmetric supercapacitors. (April 2016) - Tang, Peng-Yi; Han, Li-Juan; Genç, Aziz; He, Yong-Min; Zhang, Xuan; Zhang, Lin; Galán-Mascarós, José Ramón; Morante, Joan Ramon; Arbiol, Jordi
Abstract: Rational assembly of unique branched heterostructures is one of the facile techniques to improve the electrochemical figure of merit of materials. By taking advantages of hydrogen bubbles dynamic template, hydrothermal method and electrochemical polymerization, branched polypyrrole (PPy) nanoleaves decorated honeycomb-like hematite nanoflakes (core-branch Fe2 O3 @PPy) are fabricated. X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy (TEM), high-resolution TEM, and scanning transmission electron microscopy in high angle annular dark field mode with electron energy loss spectroscopy were combined to elucidate the mechanisms underlying formation and morphogenesis evolution of core-branch Fe2 O3 @PPy heterostructures. Benefiting from the stability of honeycomb-like hematite nanoflakes and the high conductivity of PPy nanoleaves, the resultant core-branch Fe2 O3 @PPy exhibits an ultrahigh capacitance of 1167.8 F g −1 at 1 A g −1 in 0.5 M Na2 SO4 aqueous solution. Moreover, the assembled bi-metal oxides asymmetric supercapacitor (Fe2 O3 @PPy//MnO2 ) gives rise to a maximum energy density of 42.4 W h kg −1 and a maximum power density of 19.14 kW kg −1 with an excellent cycling performance of 97.1% retention after 3000 cycles at 3 A g −1 . These performance features are superior than previous reported iron oxide/hydroxides based supercapacitors, offering an important guideline for future design of advanced next-generation supercapacitors. Graphical abstract: Highlights: 3D honeycomb-like hematite nanoflakes/branched polypyrrole nanoleaves heterostructures are fabricated. Various techniques are combined to elucidate the mechanisms underlying formation and morphogenesis evolution of core-branch Fe2 O3 @PPy heterostructures. The core-branch heterostructures facilitate the synergy of inorganic metal oxides and conductive polymers. The optimized core-branch Fe2 O3 @PPy electrode works as negative electrode and exhibits an ultrahigh capacitance of 1167.8 F g −1 at 1 A g −1 .